Putative role of prosthetic dental implants in the development of cardiac sarcoidosis: A case-control study - Subramanian, Muthiah; Bera, Debabrata; Theodore, Jospeh; Kishore, Jugal; Srinivas, Akula; Saggu, Daljeet; Yalagudri, Sachin; Narasimhan, Calambur (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2021)
Background: Etiopathogenesis of cardiac sarcoidosis is poorly understood. The objective of this study is to examine a putative role of previous dental procedures on the development of cardiac sarcoidosis(CS).Methods: Clinical details of 73 patients with CS from the Granulomatous Myocarditis Registry were analyzed. Data regarding clinical presentation, comorbidities, baseline electrocardiogram, echocardiogram and 18fluorodeoxyglucose(FDG) PET-CT was extracted from the registry database. A comprehensive history of dental procedures for all patients was recorded by the dental surgeon. The two control groups comprised of 79 patients with idiopathic ventricular tachycardia and/or complete heart block(with similar clinical presentation) and 145 healthy age and sex matched patients, respectively.Results:  Dental evaluation revealed that patients of CS had undergone a previous prosthetic dental implant (PI,p